Dark Humor in the Context of Brain Death: An Ethnographic Analysis of the Practices of Health Workers in the Metropolitan Area of Buenos Aires (Argentina) - Baranowski, Carolina Andrea (2024)
In this article, we propose to analyze how healthcare personnel involved in organ and tissue procurement activities use black humor during their daily work. The objective here is twofold: on the one hand, following previous studies, we are interested in showing the role of black humor as a way of dealing with death. On the other hand, we suggest that, in a parallel and complementary way, in this context black humor exposes a performative sense as a form of agency that attempts to modify an adverse reality. This work combines the methodological tools provided by ethnography and conducting open, multi-session interviews. The events revealed during the fieldwork and interviews that associate humor and brain death show the uses, limits and ways in which black humor operates in daily healthcare work of physical and emotional complexity.